Fire risk assessment for building operation and maintenance based on BIM technology. (November 2021) - Wang, Luqi; Li, Wenxian; Feng, Weimin; Yang, Ruiyin
Abstract: Building fires are the most common types of fires, and most fires occur during the operation and maintenance periods of buildings. A majority of the risk factors causing fire are inextricably linked to human life, which can only be controlled but not eliminated. Fire risk assessment is necessary to control fire risk and improve the preventive ability. The assessment method established in this study can scientifically calculate the fire risk value by quantifying the fire risk index of buildings. Combined with BIM technology, this method can quickly and reliably assess the fire risk of the target building model and realise the organic unity of science, effectiveness and economy. Based on the fire risk analysis method for engineering (FRAME), we propose an assessment index system for buildings in the operation and maintenance periods in terms of the potential risk level, acceptable risk level and protection level. In addition, a risk value calculation model for the operation and maintenance periods is established, and the risk value assessment standard is set to improve the firefighting ability of buildings. Furthermore, the assessment indexes are incorporated into the family attributes in Revit software to realise the information interaction between the assessment system and the model. The results show that BIM technology can be applied effectively to fire safety, to ensure that the fire risk prevention and control ability of the target has a more intuitive scientific basis. It also provides a direction and ideas for the development and application of BIM technology. Highlights: A combination of building operation and maintenance management, fire risk assessment and BIM is proposed. The function application of BIM Technology is enriched. The information interaction between the fire risk assessment system and BIM is established. Developing a model that can obtain the fire risk assessment value automatically is further research.